SCM - A Simple, Modular and Flexible Customer Interaction Management System - Schuster, Jörg; Lee, Yeong Su; Kobothanassi, Despina; Bargel, Matthias; Geierhos, Michaela (International Conference on Information Society (i-Society 2011))
SCM is a simple, modular and flexible system for web monitoring and customer interaction management. In our view, its main advantages are the following: It is completely web based. It combines all technologies, data, software agents and human agents involved in the monitoring and customer interaction process. It can be used for messages written in any natural language. Although the prototype of SCM is designed for classifying and processing messages about mobile-phone related problems in social networks, SCM can easily be adapted to other text types such as discussion board posts, blogs or emails. Unlike comparable systems, SCM uses linguistic technologies to classify messages and recognize paraphrases of product names. For two reasons, product name paraphrasing plays a major role in SCM: First, product names typically have many, sometimes hundreds or thousands of intralingual paraphrases. Secondly, product names have interlingual paraphrases: The same products are often called or spelt differently in different countries and/or languages. By mapping product name variants to an international canonical form, SCM allows for answering questions like Which statements are made about this mobile phone in which languages/in which social networks/in which countries/...? The SCM product name paraphrasing engine is designed in such a way that standard variants are assigned automatically, regular variants are assigned semiautomatically and idiosyncratic variants can be added manually. With this and similar features we try to realize our philosophy of simplicity, modularity and flexibility: Whatever can be done automatically is done automatically. But manual intervention is always possible and easy and it does not conflict in any way with the automatic functions of SCM.
Keywords: Social Media Business Integration; Contact Center Application Support; Monitoring Social Conversations; Social Customer Interaction Management; Monitoring; Software Agents

Experimentelle Untersuchung und Simulation des Crashverhaltens mechanisch gefügter Verbindungen - Hein, David; Meschut, Gerson; Hahn, Ortwin (1. Fügetechnisches Gemeinschaftskolloquium)

Power-Aware Online File Allocation in Dynamic Networks - Mehler, Jan

Stabilized Mixed Triangular and Tetrahedral Finite Elements with Volume and Area Bubble Functions - Caylak, Ismail

Mechanical and Physical Properties - A Way to asses quality of Laser Sintered Parts - Rüsenberg, Stefan; Schmidt, L.; Schmid, Hans-Joachim (22th Annual International Solid Freeform Fabrication Symposium)
The aim of this paper is the description and evaluation of physical properties like porosity and density and their influence on mechanical properties of laser sintered polyamide parts. For example, by reducing the porosity an increase of mechanical properties is possible. The correlation of laser parameters to these properties is investigated in detail. The energy density is an important parameter for the laser sintering process. By changing laser power, scan velocity and hatch distance an influence on manufactured components is given. A systematic variation of all three laser parameters is performed. A comparison of results obtained at constant energy densities obtained by varying these relevant parameters accordingly is shown as well.

Porosity as a key to increase material properties of laser sintered parts - Rüsenberg, Stefan; Schmidt, L.; Hosse, H.; Schmid, Hans-Joachim

Direct Manufacturing Design Rules - Adam, Guido; Zimmer, Detmar

Steigerung der Anlagenverfügbarkeit von Antriebssystemen durch methodische und modulare Konzeption. Modulare Konzeption von als Einzelstücke oder in Kleinserien hergestellten Antriebssystemen mit großer Nennleistung - Fiekens, Nicolas; Zimmer, Detmar (VDI/VDE-Tagung mit Fachausstellung Antriebssysteme 2011. Elektrik, Mechanik und Hydraulik in der Anwendung)

DMDR Direct Manufacturing Design Rules. Erarbeiten von applikationsunabhängigen Konstruktionsregeln - Zimmer, Detmar; Adam, Guido (Rapid.Tech 2011 Fachmesse und Anwendertagung für Rapid-Technologie)

Bestimmung der Biegesteifigkeit eines Schubgliederbandes - Zimmer, Detmar; Möller, Jens (Konstruktion - Zeitschrift für Produktentwicklung und Ingenieur-Werkstoffe)

Hybrid Planning for Self-Optimization in Railbound Mechatronic Systems - Adelt, Philipp; Esau, Natascha; Hölscher, Christian; Kleinjohann, Bernd; Kleinjohann, Lisa; Krüger, Martin; Zimmer, Detmar

Component-Based Hazard Analysis for Mechatronic Systems - Priesterjahn, Claudia; Sondermann-Wölke, Christoph; Tichy, Matthias; Hölscher, Christian (14th IEEE International Symposium on Object/Component/Service-Oriented Real-Time Distributed Computing Workshops)

Laser-sintered platform with optical sensor for a mobile robot used in cooperative load transport - Loh, Chia Choon; Trächtler, Ansgar (accepted for publication at 37th Annual Conference on IEEE Industrial Electronics Society (IECON))

Mehrzieloptimierung zur Stellgrößenermittlung für die Horizontaldynamik eines Elektrofahrzeugs mit Einzelradaktorik - Reinold, Peter; Trächtler, Ansgar (Steuerung und Regelung von Fahrzeugen und Motoren AUTOREG 2011)

Differential Dynamic Programming and the Optimal Control of Vehicle Lateral Dynamics - Khatab, Shaady; Trächtler, Ansgar (Steuerung und Regelung von Fahrzeugen und Motoren AUTOREG 2011)

Entwurfstechnik Intelligente Mechatronik - Tichy, Matthias; Oestersötebier, Felix; Schierbaum, Thomas (Internationales Forum Mechatronik)

Parametric Model-Order Reduction in Hierarchical Multiobjective Optimization of Mechatronic Systems - Krüger, Martin; Witting, Katrin; Trächtler, Ansgar; Dellnitz, Michael (18th IFAC World Congress)

Iterative learning of Stochastic Disturbance Profiles Using Bayesian Networks - Bielawny, Dirk; Krüger, Martin; Reinold, Peter; Timmermann, Julia; Trächtler, Ansgar (9th International Conference on Industrial Informatics (INDIN))

Fast Pareto set computation using algorithmic differentiation applied to the guidance of a rail-bound vehicle - Witting, Katrin; Dellnitz, Michael; Geisler, Jens; Trächtler, Ansgar; Walther, Andrea (International Conference on Simulation Technology – SIMTECH)

Verlässlichkeitsanalyse des Degradationsverhaltens mechatronischer Systeme mit mehreren Betriebsstrategien - Lurye, Oleg; Sondermann-Wölke, Christoph; Kromov, Ivan; Sextro, Walter; Trächtler, Ansgar (VDI Bericht zur Tagung Technische Zuverlässigkeit)